# 8j+4=13j-6

## Simple and best practice solution for 8j+4=13j-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 8j+4=13j-6 equation:

Simplifying
8j + 4 = 13j + -6

Reorder the terms:
4 + 8j = 13j + -6

Reorder the terms:
4 + 8j = -6 + 13j

Solving
4 + 8j = -6 + 13j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-13j' to each side of the equation.
4 + 8j + -13j = -6 + 13j + -13j

Combine like terms: 8j + -13j = -5j
4 + -5j = -6 + 13j + -13j

Combine like terms: 13j + -13j = 0
4 + -5j = -6 + 0
4 + -5j = -6

Add '-4' to each side of the equation.
4 + -4 + -5j = -6 + -4

Combine like terms: 4 + -4 = 0
0 + -5j = -6 + -4
-5j = -6 + -4

Combine like terms: -6 + -4 = -10
-5j = -10

Divide each side by '-5'.
j = 2

Simplifying
j = 2`